Bibliography of the publications of J.C. Juta and J.C. Juta and Co. 1853-1903 - Caine, A. B.; Leipoldt, L (School of Librarianship, 2017)
This is not a comprehensive bibliography of Juta publications for the period 1853 to 1903; indeed we doubt whether it is a complete record of the publications to be found in Cape Town -and no attempt has been made to trace publications in other centres. Certain sources in Cape Town have not been investigated at all, for example, advertisements in newspapers were not sought for beyond 188 3 and then the search was confined to four newspapers, published in Cape Town. A check on some of the advertisements thus found revealed that Juta's hardly advertised at all in the Eastern province during this period, but a similar check on the Dutch papers originating in Cape Town held more promise. But these researches were abandoned in favour of the more fruitful fields of Africana collections and periodicals of the time.